Educação em diabetes: capacidade e ação para o autocuidado - Cavicchioli, Maria Gabriela Secco [UNIFESP] (2010)
Introduction: The world has about 240 million people with diabetes mellitus (DM).The diabetes education has been seen as one of the mainstays of treatment. Objective: Identify the capacity (knowledge) and action for self-care in diabetes, through the application of a scale before and after an educational intervention and its relationship with the seven behaviors for diabetes education. Method: This is a correlational study with an educational intervention. We conducted a program of diabetes education (PED) during 12 months with 41 people from the private health care system and applied the Scale for Assessing Self-Care Capabilities of Persons with Diabetes (ECAD) and the Scale for Assessing the Actions of Self-Care of the Person with Diabetes (EAAD) at the beginning and end of the program. Results: There was significant improvement in glycated hemoglobin levels, glucose variability and change in diastolic blood pressure. No significant improvement was seen in lipid profile and body composition of individuals. In relation to the scales, there a significant improvement was seen in the comparison with the initial and final scores EAAD and ECAD. In the period of five years or more of diagnosis, the capacities were higher than for self-care actions, both in the initial and the final program. Regarding the seven behaviors, it was found that the healthy coping item was not included in the scale and the others, although present, would need to be broader. Conclusion: Education programs are essential to the empowerment of people with diabetes to manage their disease. It is believed that, despite the ECAD and EAAD have shown statistically significant difference between the two stages of the program, they do not include all actions necessary for the control of diabetes and prevention of acute and chronic complications.